Cyano-bridged perovskite [(CH3)3NOH]2[KM(CN)6], [M: Fe(iii), and Co(iii)] for high-temperature multi-axial ferroelectric applications with enhanced thermal and nonlinear optical performance. Issue 48 (25th November 2020) - Rok, Magdalena; Ciżman, Agnieszka; Zarychta, Bartosz; Zaręba, Jan K.; Trzebiatowska, Monika; Mączka, Mirosław; Stroppa, Alessandro; Yuan, Shurong; Phillips, Anthony E.; Bator, Grażyna
Abstract : Highly stable ferroelectrics with reversible high-temperature phase transitions and switchable nonlinear optical behaviour. Abstract : Highly stable ferroelectrics with reversible high-temperature phase transitions and switchable nonlinear optical behaviour are much coveted targets for emerging optoelectronic applications. Here, we demonstrate a cyano-bridged perovskite [(CH3 )3 NOH]2 [KCo(CN)6 ] (TMAO-Co ), a new analogue of the multi-axial ferroelectric [(CH3 )3 NOH]2 [KFe(CN)6 ] (TMAO-Fe ) with improved thermal stability and enhanced second-order nonlinear optical response. Indeed, for TMAO-Co the Curie temperature ( T c ) is shifted to a higher value of ca. 416 K (improvement by ca. 10 K versus TMAO-Fe ); the separation between T c and the decomposition threshold is 46 K. TMAO-Co is a biaxial ferroelectric as revealed by P ( E ) hysteresis loop measurements along the a and c crystallographic directions with spontaneous polarization values of 0.9 and 0.63 μC cm −2 at 293 K, respectively. The SHG response of TMAO-Co is two times higher than that of TMAO-Fe . The improved stability of TMAO-Co to thermal and optical loads allowed for demonstration of bistable switching of nonlinear optical response between SHG-on and SHG-off states by temperature sweeping. Structurally, TMAO-Co reproduces the unusual characteristics of TMAO-Fe, i.e. the first-order phase transition between (polar) monoclinic to (nonpolar) cubic phases involving bond switching and is assisted by the pronounced increase of disorder of the TMAO cations above T c . Combined temperature-resolved Raman and infrared spectroscopic measurements were employed to track the symmetry increase above T c, which is primarily associated with changes in hydrogen-bonding. Consistent with the bond-switching character of the phase transitions, a pronounced shift to higher wavenumbers is observed for the O–H stretching modes. The DFT calculations demonstrate that the system's polarization along the a -axis mostly comes from the rotation of the [(CH3 )3 NOH]2 cluster, while the atomic displacement of the framework contributes largely to that along the c axis.